A Rare Case of Caecal Desmoid Tumor - Anas Elwassi; Khalid Jamaleddine; Ayoub Amor; Kenza Benjelloune; Amal Hajri; Driss Erguibi; Rachid Boufettal; Saad Jai Rifki; Farid Chehab (European Scientific Journal, ESJ, 2024)
Desmoid tumors (DT) are locally aggressive fibromatoses with no metastatic potential. They represent rare soft-tissue tumors arising from musculoaponeurotic structures. Most intra-abdominal desmoid tumors occur in the mesentery and peritoneum, whereas caecal desmoid tumors are extremely rare. We report the case of a 16-year-old woman who presented with abdominal pain localized in the right lower quadrant, along with chronic constipation evolving over 8 months. MRI demonstrated a 126x117x68 mm abdomino-pelvic mass, suggesting a gastrointestinal stromal tumor (GIST). The patient was prepared for surgery, and intraoperative exploration demonstrated a large tumor of the caecum. Right hemicolectomy was performed, and histopathology confirmed a caecal desmoid tumor. The postoperative follow-up was normal, and the patient is well 6 months postoperatively.